Marine Pollution Supervision and Performance of Harbourmaster on Shipping Safety - Muhammad Taris Hasibuan; Gatot Cahyo Sudewo; Andjar Budi Wibawanti; Isa Amsyari; Edhie Budi Setiawan; Zaenal Abidin (Institut Transportasi dan Logistik Trisakti, 2022)
The purpose of this study is to identify the number of incidents of marine pollution caused by the disposal of dirty oil waste from commercial ships docked and berthed at the pier as a result of marine pollution. This study will also investigate whether they have an impact on the disruption of shipping safety and the marine environment. The method of data analysis is Structural Equation Modelling with Smart PLS version as its tool. The population in this study was 131 officers in the field of guarding, patrolling, and investigating. A sample of 99 respondents was obtained using the Slovin formula. The results show that the supervision of marine pollution has a positive effect on the performance of the harbormaster. Marine pollution supervision can improve the harbourmaster’s performance and positively impact shipping safety. Marine pollution supervision should be maintained, improved, and consistent, and make modern system breakthroughs so that the safety of marine transportation will be fulfilled and guaranteed.